A dedicated skin-to-brain circuit for cool sensation in mice - Hankyu Lee; Chia Chun Hor; Lorraine R. Horwitz; Ailin Xiong; Xin-Yu Su; Daniel R. Soden; Sarah Yang; Wei Cai; Wenwen Zhang; Chen Li; Christopher Radcliff; Abbey Dinh; et al. (Nature Communications)
Abstract Perception of external temperature is essential for maintaining homeostasis and avoiding thermal injury. Although molecular thermosensors such as transient receptor potential melastatin type 8 (TRPM8) have been identified, the neural circuits responsible for transmitting cool signals remain unclear. Here we show that a spinal circuit in mice conveys cool signals from the skin to the brain. Excitatory interneurons in the spinal dorsal horn expressing thyrotropin-releasing hormone receptor (Trhr+) act as a central hub for cool sensation. These Trhr+ neurons receive monosynaptic input from TRPM8+ sensory afferents and are selectively activated by innocuous cool stimuli. Ablating Trhr+ interneurons abolishes behavioral responses to cool, but not to warm or cold stimuli. We also identify a population of calcitonin receptor-like receptor-positive (Calcrl+) spinal projection neurons that receive convergent input from both TRPM8+ afferents and Trhr+ interneurons, and transmit cool-specific signals to the lateral parabrachial nucleus (lPBN). Our findings define a feedforward amplification circuit for cool sensation and reveal a modality-specific spinal pathway for thermal processing.